The Comparison of Visual Acuity between Spectacles and Rigid Gas Permeable (RGP) Group in Myopia Patients: Poster Presentation - Observational Study - Resident - Havilah Zeki Rosa; Rinda wati (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : The prevalence of myopia has approximately doubled in the past three decades, with rates of 70–87% among populations of school children and young adults in Asia. Approaches to treating myopia include spectacles and Rigid Gas Permeable (RGP) contact lenses. RGP has become a new "preference" because it is more comfortable and provides a more aesthetic look. This study aims to determine which method is better for correcting visual acuity in myopia patients. Methods : This cross-sectional study analyzed the outcomes and exposures measured at the same time. The sample included myopia patients (based on spherical equivalent) who underwent RGP contact lens fitting in the refraction outpatient clinic of M Djamil Hospital from January 2021 to December 2022. The samples were selected based on inclusion and exclusion criteria. The collected data included gender, age, and best-corrected visual acuity using spectacles and RGP. Results : Forty-three patients were eligible as the sample in this study. Most of the subjects were women (62.8%), and the mean age was 23.58 years old. The median LogMAR for the RGP group was lower than the spectacles group (0.00:0.10 on both eyes). Statistical analyses found a significant visual acuity improvement in the RGP group compared to the spectacles group in both the right and left eyes (p = 0.014 and p = 0.005, respectively (p < 0.05)). Conclusion : The use of RGP provides significantly better visual acuity in correcting myopia than spectacles. Myopia is more frequently found in young women.